E-197 Pulserider for aneurysm re-treatment: combined sub-analysis of the ANSWER and AWARD studies. (4th August 2020) - Spiotta, A; Lopes, D; Mocco, J; Siddiqui, A; Tateshima, S; Nahser, H
Abstract : Introduction: PulseRider is a neck bridging device designed to aid in coiling of wide-neck intracranial aneurysms. When in place, it provides a 'floor' to the coil mass while allowing for easy access to the aneurysm sac, making it potentially suited for retreatment cases with limited working space. Methods: Procedural success and outcomes of retreatment cases included in the AWARD (Safety Study of the PulseRider in Patients Undergoing Treatment for Bifurcation Intracranial Aneurysms) and ANSWER (Adjunctive Neurovascular Support for Wide-neck aneurysm Embolization and Reconstruction) studies are presented. Results: Eleven PulseRider cases (10 female, mean age 50.9 years), 6 in AWARD and 5 in ANSWER, were retreatments of previously coiled aneurysms. Eight of the patients had 1 previous procedure, 2 had 2 previous treatments, and 1 had 3, including a failed attempt at Y-stenting. Mean aneurysm neck size was 4.98 mm (range 3.0–11.6 mm). Locations included basilar (7), carotid terminus (2) and MCA (2). PulseRider was successfully implanted with the ability to retain coils within the aneurysm in all cases. Immediately post-procedure, core lab adjudicated adequate occlusion rate was 91% (4/11 [36%] RR-I, 6/11 [55%] RR-II and 1/11 [9%] RR-III). At the one year follow up, the adjudicated rate of adequate aneurysm occlusion was 80% (6/10 [60%] RR-I, 2/10 [20%] RR-II, and 2/10 [20%] RR-III). There were no neurological deaths or major ipsilateral stroke (primary safety endpoint in the ANSWER study) and neurological decline was noted in one patient (the case of 3 previous treatments). Conclusion: Retreatment of previously coiled wide-neck aneurysms with the PulseRider device resulted in 100% procedural success and 80% complete or near complete occlusion at 1 year with an acceptable safety profile. Disclosures: A. Spiotta: 1; C; Microvention. 2; C; Penumbra, Minnetronix, Cerenovus. 6; C; Cerenovus, Penumbra, Microvention. D. Lopes: None. J. Mocco: 2; C; Rebound Medical, LLC, Cerebrotech Medical Systems, Inc., Snchroyn, Inc., EndoStream Medical, Ltd.. 4; C; Apama Medical, Inc., NeuroTechnology Investors, LLC., NeurVana Medical, LLC, Cerebrotech Medical Systems, Inc., Synchron, Inc., EndoStream Medical, Ltd., Stroke Project, Inc. A. Siddiqui: 2; C; Amnis Therapeutics, Boston Scientific, Canon Medical Systems USA, Cerebrotech Medical Systems, Claret Medical, Corindus, Endostream Medical, Guidepoint Global Consulting, Imperative Care, Integra, Rapid Medical, Rebound Therapeutics Corp., Silk Road Medical, StimMed, Stryker, Three Rivers Medical, VasSol, W.L. Gore & Associates, Cerenovus, Medtronic, MicroVention, Penumbra, Medical University of South Carolina, National PI/Steering Committee for POSITIVE Trial, Northwest University, DSMB Chair for HEAT Trial. 4; C; Amnis Therapeutics, Apama Medical, BlinkTBI, Buffalo Technology Partners, Cardinal Health, Cerebrotech Medical Systems, Claret Medical, Cognition Medical, Endostream Medical, Ltd, Imperative Care, International Medical Distribution Partners, Rebound Therapeutics Corp, Silk Road Medical, StimMed, Synchron, Three Rivers Medical, Viseon. S. Tateshima: 2; C; Cerenovus, Medtronic, Neurovasc, Stryker. 4; C; Neurovasc. H. Nahser: None.